Mongolia : Background Material. - International Monetary Fund. (Washington, D.C. : International Monetary Fund, 1996)
This paper describes economic developments in Mongolia during the 1990s. Real GDP growth accelerated to 6 percent in 1995, the second year of positive growth since the transition to a market economy commenced. The main impetus to growth was again provided by the strong performance of agriculture, industry, mining, and construction. There was a record increase in livestock population, mainly in the more valuable cashmere goats. The number of new private industrial enterprises continued to grow, while ownership and management changes at some large state-owned enterprises helped stem the decline of output in that sector.
Off-Campus Access: No User ID or Password Required
On-Campus Access: No User ID or Password Required
Mode of access: Internet